L'UE estime les négociations d'APE suffisamment avancées - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Selon un communiqué de presse de l'UE, le Conseil des ministres ...